Niosomal Bupropion: Exploring Therapeutic Frontiers through Behavioral Profiling - Karthick Harini; Suliman Yousef Alomar; Mohammed Vajagathali; Salim Manoharadas; Anbazhagan Thirumalai; Koyeli Girigoswami; Agnishwar Girigoswami (MDPI AG, 2024)
Bupropion (Bup) belongs to the norepinephrine-dopamine reuptake inhibitor (NDRI) class and it is the only FDA-approved drug of its class for the treatment of major depressive disorder (MDD), sold under the name of Wellbutrin. Although bupropion is effective in suppressing the symptoms, its regular use and overdose might lead to seizures and liver failure. Thus, we aimed to nanoformulate bupropion onto a niosomal vesicle to improve its efficacy and achieve the same therapeutic effect at lower scheduled doses. A thin film hydration method was adopted to synthesize and optimize Bup entrapped niosomes using three different surfactants of the sorbitan ester series (Span 20, 40, and 60) in combination with cholesterol. The optimization data determined that the niosome formulated with a cholesterol-to-surfactant ratio of 1:1.5 is the most stable system, with the Bup entrapped niosomes containing Span 20 (Bup@N20C) exhibiting minimal in vitro and in vivo toxicity, and demonstrating the sustained release of Bup in artificial cerebrospinal fluid (ACSF). The Bup@N20C formulation showed increased exploration activity and reduced irregular movements in reserpine-induced depression in the adult zebrafish model, suggesting the potential for mood improvement through the suppression of depression-like behavior which was established by statistical analysis and trajectory data. The Bup@N20C-treated group even surpasses the treatment effect of the positive control group and is comparable to the control group. Hence, it can be inferred that niosomal formulations of Bup represent a promising delivery system capable of achieving the brain delivery of the cargo by bypassing the blood-brain barrier facilitated by their small architectural structure.